Az y-generáció elvárásai, kommunikációja egy debreceni szervezetnél - Juhász, Csilla (Közép-Európai Közlemények, 2014)
Our essay and survey target was to reveal some difference in expectancies and communication of Generation Y. The phrase Generation Y first appeared in an August 1993 Ad Age editorial to describe teenagers of the day, which they defined as different from Generation X, and then aged 12 or younger as well as the teenagers of the upcoming ten years. Since then, the company has sometimes used 1982 as the starting birth year for this generation. We studied 20-30 years old emloyees, who works at multinational organization. We studied prevelance and form of communication. We also studied expectational possibilities, these were the following: creativeness of work, variety of job, variety of task, possibility of self-reallisation, chal- lenges, supported vocational development, possibilities of carreer. Our results showes, that women are not so more carrieristic than men. They appraised more professional challenges and development in profession. Between the ages there are no determining differences also.